Employability Skills Needed by Vocational College Graduates: Feedback From the Industry - Haron, Mohd Adib; Mohammad Hussain, Mohammad Azlan; Mohd Zulkifli, Rafeizah; Mat Nashir, Irdayanti; Imam Ma'arof, Nurul Nazirah (Journal of Technical Education and Training, 2019)
In the real industrial setting, job duties and skills requirement have changed so much that makes seeking for employment can be a challenging experience. Hence, new graduates need to have the right skills at the right place, and at the right time. This study has been conducted to identify the employability potential of Malaysian Vocational College (KV) graduates based on the current employer perception. In addition, the employability skills among KV graduates as perceived by their potential employers will be identified, so an action can be suggested to KV stakeholders to better prepare their graduates. This study used a descriptive research design with a quantitative approach. The quantitative data for this study were obtained through questionnaires, developed based on the related literature review. The population size of the study is 882 industrial employers, who were involved in On the Job training (OJT) program of the first batch of KV students (from a pilot program). Stratified random sampling techniques were used to select the sample, which came out with a total of 269 sample size. The result of the study shows that communication, thinking and problem-solving skills were perceived as very important by industrial employers, so it has been suggested for the KV management team to develop their students with those attributes before they proceed to the job seeking process.